2004
DOI: 10.1111/j.1432-1033.2004.04261.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of porphyrin binding to Momordica charantia (bitter gourd) lectin

Abstract: Owing to the use of porphyrins in photodynamic therapy for the treatment of malignant tumors, and the preferential interaction of lectins with tumor cells, studies on lectinporphyrin interaction are of significant interest. In this study, the interaction of several free-base and metalloporphyrins with Momordica charantia (bitter gourd) lectin (MCL) was investigated by absorption spectroscopy. Difference absorption spectra revealed that significant changes occur in the Soret band region of the porphyrins on bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 51 publications
(77 reference statements)
1
26
0
Order By: Relevance
“…6). It is pertinent to note here that CD spectroscopy shows that binding of porphyrins to MCL also does not result in significant changes in the secondary and tertiary structures of the protein (19).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…6). It is pertinent to note here that CD spectroscopy shows that binding of porphyrins to MCL also does not result in significant changes in the secondary and tertiary structures of the protein (19).…”
Section: Discussionmentioning
confidence: 90%
“…Detailed thermodynamic analysis of porphyrin binding to two Cucurbitaceae seed lectins, namely TCSL and MCL indicated that while the TCSL-porphyrin interaction is primarily stabilized by entropic factors (18) binding of porphyrins to MCL is mediated by strong enthalpic forces, with negative contribution from entropy of binding (19). Single-crystal X-ray diffraction studies on the interaction of H 2 TSPP with different lectins, viz., Con A, jacalin and peanut agglutinin (PNA) have revealed distinctly different modes of interaction between the lectin and the porphyrin (4, 20 -22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another example is the interaction of water soluble freebase and metalloporphyrins (639a/b, 640a/b, 641a and 74) with Momordica charantia (bitter gourd) lectin (MCL), a tetrameric galactose-specific glycoprotein. Here, significant changes in the Soret band region of the electronic absorption spectra of the porphyrins were observed upon binding to MCL [390] . The association constants for the interaction of different porphyrins with MCL at 25 °C varied between 5×10 3 M -1 and 10 5 M -1…”
Section: Lectin Bindingmentioning
confidence: 85%